Dispersed information on regional integration - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Information on regional integration in ACP countries is widely scattered. And it is not easy to find documents which offer an up-to-date picture of this very topical issue. But the on-line study Processes of regional economic integration serves as a good